Zollrecht in Japan - Zitzmann, Monika; Fahje, Arne (Zeitschrift für Japanisches Recht, 2007)
This article offers an overview of Japanese customs law. After a short introduction in which the history of customs law is touched upon, the various laws containing provisions on customs are introduced. In the following chapters, the authors deal with the organization of the Japanese customs authorities and the different functions of customs. Customs clearance, the question as to when customs debts arise, and how customs are charged are further major issues addressed. The authors also point out provisions dealing with violations of customs law. The article concludes with a few words on the particularities of trade between the EU and Japan. (Translation by the Editors)